CONTROL SYSTEM PROTOTYPE DESIGN OF ASYMMETRIC CONVERTER FOR 12 SLOT 8 POLE 5KW 3000 RPM SWITCHED RELUCTANCE MOTOR DRIVE - Parulian Tulus Situmora, Joshua
This research discusses the control system prototype of an asymmetric converter for a three-wheeled electric vehicle (e-trike) with a switched reluctance motor. The control system used in this research is PI, PWM, and hysteresis controller. With these controllers, two modes and two features can be modelled in MATLAB, they are forward mode, reverse mode, cruise control, and regenerative braking. The forward and reverse mode is a driving mode where the vehicle will move forward or backward by controlling the starting angle to 22.5o or 0o, on both modes minimalization of the torque ripple are prioritized so the conduction angle is set to 22.5o. The cruise control feature is a system where the vehicle’s speed is maintained at a constant value using a PI based speed control. The regenerative braking feature is a control system where the power flows to the battery during braking by applying current on the opposite angle.